2004
DOI: 10.1111/j.1365-2591.2004.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional observation of pulp cavities in the maxillary first premolar tooth using micro‐CT

Abstract: Morphological features of the pulp cavity of maxillary first premolar teeth in different age groups were observed three dimensionally using micro-CT. Decreases in pulp cavity size and shape with age were clarified using a three-dimensional technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 14 publications
4
53
0
5
Order By: Relevance
“…MCT is non-destructive and a very accurate and useful tool with which to study external and internal tooth anatomy. Parallel findings have been previously reported using MCT to study external and internal tooth morphologies (30,31) and periradicular bone destruction (32,33). Moreover, our current technique overcomes the shortcomings of previously reported techniques (16,22).…”
Section: Discussionsupporting
confidence: 69%
“…MCT is non-destructive and a very accurate and useful tool with which to study external and internal tooth anatomy. Parallel findings have been previously reported using MCT to study external and internal tooth morphologies (30,31) and periradicular bone destruction (32,33). Moreover, our current technique overcomes the shortcomings of previously reported techniques (16,22).…”
Section: Discussionsupporting
confidence: 69%
“…Studies using the micro-CT have started to be used in many fields of clinical dentistry. [13][14][15][16][17][18][19][20][21][22] It is thought to be especially useful in studying the morphology of pulp cavity which can not be directly observed by the naked eye. Two-dimensional image obtained from the micro-CT distinguishes the difference in level of calcification as difference in X-ray translucency.…”
Section: Discussionmentioning
confidence: 99%
“…Oi et al 14) reported three-dimensional morphological change with age in the pulp chamber of maxillary first premolars by observing and calculating the volume ratio of the pulp chamber and root bifurcation of the root cavity. Iwaka 8) also performed the same research using mandibular first molars as samples.…”
Section: Introductionmentioning
confidence: 99%